SECOND GENERATION DRUG-ELUTING STENT IMPLANTATION FOLLOWED BY SIX- VERSUS TWELVE-MONTH DUAL ANTIPLATELET THERAPY (Неотложная медицинская помощь)
Colombo A., Chieffo A., Frasheri A., et al. Second-Generation Drug-Eluting Stent Implantation Followed by 6- Versus 12-Month Dual Antiplatelet Therapy: The SECURITY Randomized Clinical Trial // J. Am. Coll. Cardiol.– 2014. – Vol. 64. – P. 2086–2097.